Supporting the well-being of new university teachers through teacher professional development - Gast, Inken; Neelen, Madelief; Delnoij, Laurie; Menten, Marloes; Mihai, Alexandra; Grohnert, Therese (Frontiers in Psychology, 2022)
Over the last decades, changes within higher education have created increased pressure and uncertainty for academics, increasing their risk for cognitive, behavioral, physical, as well as psychological issues due to high job demands. Specifically, for new academics in teaching roles, their lack of knowledge and skills can contribute to a negative effect of these job demands on their well-being. This study therefore explored how teaching-related professional development programs can enhance new university teachers’ well-being, through semi-structured interviews with 10 university teachers participating in such a program at a mid-sized Dutch university. We pay special attention to the relationship between specific learning activities integrated in the program (such as learning communities, formal workshops, and reflecting) and various dimensions of the psychological model of well-being by Ryff and Keyes (such as self-acceptance, autonomy, environmental mastery, and positive relationships). Using co-occurrence analysis and content analysis, we found that different learning activities had distinct relationships with different well-being facets. For example, formal workshops were mainly related to environmental mastery, a purpose in life and personal growth, while reflecting seemed to be especially connected to teachers’ self-acceptance, and participating in a learning community was mainly related to positive relations with others and personal growth. Our findings have implications for research on teacher well-being as well as for the design of professional development programs for higher education teaching staff.